1992
DOI: 10.1063/1.107622
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effects on heavily carbon-doped GaAs

Abstract: The hole concentrations and lattice mismatch with the GaAs substrate of heavily carbon-doped epilayers (4.7×1019 and 9.8×1019 cm−3) were increased and the mobilities were decreased as compared with the as-grown samples by rapid thermal annealing silicon nitride capped samples at temperatures from 500 to 900 °C. However, for the more heavily doped sample, the hole concentration, mobility, and lattice mismatch decreased with increasing annealing temperature for annealing temperatures higher than 700 °C, but the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…(13) and (14) and the thermal equilibrium PAs 4 values given by Arthur [20] for GaAs crystals with compositions at the thermodynamically allowed Ga-rich limits. Equation (15) approximately fits the present Ds(Ga-rich) data.…”
Section: D=d(c/ )(7)mentioning
confidence: 62%
See 1 more Smart Citation
“…(13) and (14) and the thermal equilibrium PAs 4 values given by Arthur [20] for GaAs crystals with compositions at the thermodynamically allowed Ga-rich limits. Equation (15) approximately fits the present Ds(Ga-rich) data.…”
Section: D=d(c/ )(7)mentioning
confidence: 62%
“…Using AlAs/GaAs SL, a few studies on the effect of carbon doping on Al-Ga interdiffusion have been conducted, but the results are not consistent [3][4][5]. The CA, diffusivity values have been measured [1,[5][6][7][8], and hole concentrations in carbon-doped GaAs and SL crystals have been reported to decrease when annealed at temperatures higher than -600°C [6,7,[9][10][11][12][13][14][15]. However, the CA s diffusion and hole reduction mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 98%
“…Several papers report that hydrogen deactivates the incorporated carbon so that the hole concentration is given by [C]À[H] [36][37][38]. The open circles in Fig.…”
Section: Hydrogen Incorporationmentioning
confidence: 98%
“…(Enquist, 1992) Transmission electron microscopy (TEM) of annealed epitaxial layers which were heavily doped with C and show a significant reduction of free carrier concentration showed no evidence of the formation of dislocations. (Han, et al, 1992) (Han, et al, 1992) Although dislocations were not seen with TEM the strain was relieved in the epitaxial layers following annealing.…”
mentioning
confidence: 99%
“…(Han, et al, 1992) It is further suggested that these dislocations have electrical character (donor) which compensate the C acceptors. It is unlikely that dislocations would exist in heavily C doped GaAs and that they would create a sufficient concentration of electrically active donors to compensate C acceptor cocentrations greater than 1 Q20 cm-3.…”
mentioning
confidence: 99%